Understanding the Effects of Cardamom Cultivation on Its Local Environment Using Novel Systems Thinking Approach-the Case of Indian Cardamom Hills - Murugan, Muthusamy; Ashokkumar, Kaliyaperumal; Alagupalamuthirsolai, M.; Anandhi, Aavudai; Ravi, Raju; Dhanya, M. K.; Sathyan, Thiravidamani (Frontiers in Sustainable Food Systems, 2022)
Intensive cardamom cultivation in Indian cardamom hills (ICH) has been related to severe ecological and environmental implications that can challenge the long-term sustainability of cardamom. This research study and analysis proposes a novel system thinking approach for sustainable agroecological production of cardamom in southern India. The effects of intensive cardamom cultivation on its forest environment had been significant. A considerable increase in surface air and temperature was observed in the ICH during the last three decades (1990-2020). Cardamom hill reserves (CHR) climate has a very high variability of daily cycles (surface air temperature and relative humidity) compared to low variability of yearly cycles, which helped minor and major pests and diseases occur and spread throughout the season. The current hydrothermal condition of the soil fostered the occurrence of soil insect pests, resulting in higher pesticide use. Epiphytes peculiar to the CHR forest have been eliminated due to repeated, intense shade lopping of each tree. Variability occurred in cardamom growth as well as development and yield can be assigned to changes in the microclimatic environment prevailing in the micro habits of the sloping hillsides. The present has study brought out the possible linkages and various dimensions of the intensive growing practices that positively reflected in its local climate and production system. Shade level influences the cardamom microclimatic conditions inside the cardamom canopy which at 75% shade level, the relative humidity close proximity with panicle was maximum (88.9%), and the mean air temperature was minimum (18.4°C). On the contrary, the relative humidity at canopy top was reduced (78.7%) but the mean air temperature was still high (27.4 °C). This study also suggests that future energy transfers in the CHR production system must be understood for improving the long-term agricultural sustainability of cardamom cultivation in the ICH.